Use of the flipped classroom for the development of autonomy and critical thinking: Application in Students of the University Technician in English Language of the Technological University of Queretaro. - Mejía Velázquez, María Paulina; Reyna Lara, Griselda Patricia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Currently education requires autonomy in student learning. For this reason, the following research was carried out using the flipped classroom as a methodology to improve the autonomy of students in subjects such as Human Development, Assessment Instruments and English Language Teaching Strategies.Since September 2021, the students of the educational program of Associates Degree in English Language Teaching, worked in a hybrid way. For this reason, the flipped classroom methodology was a useful tool to develop the skills required by the educational program, in addition to autonomy.